What will future physicians do when they face with ethical dilemmas? An overview of forensic medicine internship guidance - Yıldız, Abdulkadir; Gürpınar, Süleyman Serhat; Eroğlu, İbrahim and Cinkara, Osman and Aldemir, Fatma Nur (The Bulletin of Legal Medicine, 2022)
Objective: In this study, the guidance of forensic medicine education to medical students on ethical dilemmas and its effect on their attitudes and behaviours on ethical approach were examined, at the same time, common ethical dilemmas tried to be solved through discussion. Methods: A survey, trying to determine the attitudes and behaviors of the students in the face of possible scenarios including ethical dilemmas in their medical professional life, was applied on 111 volunteer participants covering fifth semester medical students. “SPSS for Windows 17.0” package program was used to analyze the acquired data. Results: It was observed that medical faculty students taking forensic medicine internship training stated that they would present a statistically significant level of ethical approach compared to those not taking forensic medicine internship training in all six scenarios with ethical dilemma (Scenarios 1, 2, 4, 5, 6 p<0.01 / Scenario 3 p<0.05). Conclusion: Ethical dilemmas are the significant issues that a physician will often encounter throughout his career. Physicians should solve these dilemmas by knowing about their ethical responsibilities and the national and international regulations on these responsibilities. Thus, teaching about the medical ethics and these regulations in medical education have a particular importance. It was thought that there should not be such a significant difference of an ethical approach among the students in the same period of their education process. Since ethic is the common ground of all medical branches, each branch should include the education of ethic in its curriculum.